Management of ductal sialolith simplified: A new technique - Koijam Sashikumar Singh (Wolters Kluwer Medknow Publications, 2020)
Sialolithiasis is a common salivary gland disease. It may cause swelling of the gland, infection of the gland, or even death of glandular parenchymal cells. Various treatment modalities are available for management of sialolithiasis such as extracorporeal shock wave lithotripsy, sialoendoscopy, laser intracorporeal lithotripsy, interventional radiology, the video-assisted conservative surgical removal of the parotid, and submandibular calculi. These sophisticated procedures may not be available in all health-care centers. In this article, a new simple yet precise technique for management of ductal sialolith with minimum armamentarium is introduced.